2016
DOI: 10.1089/bio.2015.0060
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Apoptosis After Hypothermic Storage of a Pancreatic β-Cell Line

Abstract: Insulin-dependent diabetes mellitus is one of the leading causes of death world wide. Donor-derived pancreas and islet of Langerhans transplantation are potential cures, however, postmortem ischemia impacts islet quality. The murine bt3 cell line was used as a model to study apoptosis after hypothermic storage by comparing UnisolÔ with Belzer's machine perfusion solution (BMPS) and the University of Wisconsin (UW) solution. The objective was to determine which of these solutions provided the best support for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…3,4 Many efforts have been made to extend the islet ex vivo lifetime by exploiting the storage time, temperature, culture solution components, and methods. 5,6 Many studies compared the effect of temperature on the islet preservation, and there is still a lack of consensus. 7 Hypothermic preservation in a short time (<7 days) is commonly applied in research and clinical islet transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Many efforts have been made to extend the islet ex vivo lifetime by exploiting the storage time, temperature, culture solution components, and methods. 5,6 Many studies compared the effect of temperature on the islet preservation, and there is still a lack of consensus. 7 Hypothermic preservation in a short time (<7 days) is commonly applied in research and clinical islet transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Hypothermic preservation in a short time (<7 days) is commonly applied in research and clinical islet transplantation. 6 Many additives in storage solution have been reported to improve the recovery and functions of preserved islets, and among them, antioxidative and anti-inflammatory ingredients showed superior advantages. [8][9][10] As mentioned, hypoxiainduced oxidative stress is one of the primary causes of the apoptosis and dysfunction of preserved islets.…”
Section: Introductionmentioning
confidence: 99%
“…Preservation solutions, regardless of whether they are designed to be intracellularor extracellular-type solutions, contain various components that aim to ameliorate ischemia/reperfusion injury, including (1) buffer systems to prevent acidosis, (2) oncotic active agents that prevent intracellular water influx and thus cell edema and swelling, (3) high-energy compounds that provide substrates for regeneration during cold storage and upon reperfusion, and (4) antioxidants to mitigate oxidative stress [18][19][20]. Unisol contains HEPES, a zwitterion buffer effective for pH control in cold temperatures; large molecules lactobionic acid, gluconate, and dextran with oncotic activity; and glucose, sucrose, and adenosine as energy substrates (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Unisol has thus far been investigated for preservation of pancreatic beta-cells and in the setting of swine clinical suspended animation [18,20]. For beta-cells, Campbell et al demonstrated superior cell viability, and lower levels of apoptotic activity in Unisol-stored cells compared to ones stored in UW and Belzer's machine perfusion solution [18,19].…”
Section: Discussionmentioning
confidence: 99%